Speaking of Economics: How to Get in the Conversation (an excerpt) - Arjo Klamer (Journal of Economic Sociology, 2014)
In his book “Speaking of Economics: How to Get in the Conversation” Arjo Klamer continues the conversation about economics, initiated in his previous influential books, including “Conversations with Economists” [Klamer 1983]. “Speaking of Economics” aims to explain who economists are and what they do. Klamer claims that economists are not inclined to get into interaction. That is explained by a number of reasons. For instance, economists often hold different views on the same issues. In addition, economists apparently prefer to talk mathematics and statistics to real-world topics.Economists’ fragmentation and disinclination to exchanges slows down the development of economics. Thus, the author proposes to consider economics, or the world of economists, as a conversation or a bunch of conversations. His approach to economics is aimed at shedding light on the necessity for interaction between different economists and bridging the gap between economists and other external worlds, including politics.The Journal of Economic Sociology publishes the book’s conclusion “Peroratio: Why the Science of Economics Is Not All That Strange”, where Klamer summarizes the main ideas. He demonstrates that the metaphor helps to see the four gaps: epistemological; rhetorical; in everyday economics and in the world of politics.